The Effect Of Using Brainpop Learning Media on The Ability to Write Short Story Texts of Grade XI Students - Rohayana Sormin; Sarma Panggabean; Renita br Saragih (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
The purpose of this study is to determine how the use of Brainpop media affects the ability to write short story texts in class XI students of SMA Negeri 17 Medan. The population in this study was all class XI students of SMA Negeri 17 Medan in the 2025/2026 academic year consisting of 8 classes totaling 284 people, from this population a sample of 35 people was determined, namely class XI B which was selected by simple random samplingThe method used in this research is a one group pretest-posttest design with the problem and research objective to determine students' short story writing skills and to obtain the data, the instrument used is an assignment test.From the data analysis, the results of the pretest for students before using Brainpop media showed that the average score for students was 50, while the results of the posttest for students after using Padlet media showed that the average score for students was 74.The results of the hypothesis test using the t-test obtained a calculated t value = 13.874 while the t table value at a significance level <= 0.05 was 1.667572, therefore the obtained t count> t table (13.874 1.667572) so the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected.Based on the research results, it can be concluded that using Brainpop media is effective in writing short story texts for class XI students of SMA Negeri 17 Medan in the 2025/2026 academic year. Keywords: Brainpop Media, Short Story Writing Ability.